“Japa’’ syndrome: Mediating role of organizational climate on psychological contract breach and turnover intention - Fagbenro, Dare Azeez; Yusuff, Ridwan O.; Ariyo, Oluwaseyi C. (Academic Journal of Psychology and Counseling, 2025)
In Nigeria, the continuous exodus of health workers, known as ’Japa’, and the intention of many to leave their current jobs is worrisome and needs urgent attention. This study investigated the role of psychological contract breach on turnover intention. The study also further examined the mediating role of organizational climate in the relationship between psychological contract breach and turnover intention among health workers. The study adopted a cross-sectional study with a total of 146 health workers aged 20-59 years (male=29.5%, female=70.5%; M age=34.80). The study found that psychological contract breach has a positive correlation with turnover intention, but the correlation is negative with organizational climate. Organizational climate was also found to have a negative relationship with turnover intention, while organizational climate partially mediates the positive relationship between psychological contract breach and turnover intention. The study concluded that psychological contract breach fuels turnover intention, while organizational climate serves as a buffer between psychological contract breach and turnover intention. Therefore, efforts promoting a favorable organizational culture can help improve and sustain employees' psychological agreements, which may help reduce turnover intention among health workers.